Methodological aspects of creating frames for low-power vehicles (ATVS) based on tubular profiles - Dalida N.V.; Filkin N.M.; Scuba D.V. (Научно-технический вестник Брянского государственного университета)
The paper discusses the main methodological aspects of creating a carrier system (frame) of a lowpower vehicle (quad-cycle) based on tubular profiles. The basic requirements for the frame of the ATV, the issues of the layout of the ATV based on the basic three points are considered. The requirements for the ATV frame are proposed, taking into account the possibilities of unification of design elements and modernization of the structure in the future when creating other models of tires. The analysis of consumer properties for the ATV and the influence of these properties on the design of the designed machine is carried out. A simplified algorithm for the development of a low-power vehicle frame is proposed, and it is also proposed to extend the cubic shape method to the ATV design process. The accuracy requirements for various methods of assembly of tubular parts of the ATV carrier system are considered.